Standardizing the Development of Serious Games for Physical Rehabilitation: Conceptual Framework Proposal - María Del Pilar Beristain-Colorado; Jorge Fernando Ambros-Antemate; Marciano Vargas-Treviño; Jaime Gutiérrez-Gutiérrez; Adriana Moreno-Rodriguez; Pedro Antonio Hernández-Cruz; Itandehui Belem Gallegos-Velasco; Rafael Torres-Rosas (JMIR Publications, 2021)
BackgroundSerious games have been used as supportive therapy for traditional rehabilitation. However, most are designed without a systematic process to guide their development from the phases of requirement identification, planning, design, construction, and evaluation, which reflect the lack of adaptation of rehabilitation requirements and thus the patient's needs. ObjectiveThe aim of this study was to propose a conceptual framework with standardized elements for the development of information systems by using a flexible and an adaptable process centered on the patient's needs and focused on the creation of serious games for physical rehabilitation. MethodsThe conceptual framework is based on 3 fundamental concepts: (1) user-centered design, which is an iterative design process focused on users and their needs at each phase of the process, (2) generic structural activities of software engineering, which guides the independent development process regardless of the complexity or size of the problem, and (3) gamification elements, which allow the transformation of obstacles into positive and fun reinforcements, thereby encouraging patients in their rehabilitation process. ResultsWe propose a conceptual framework to guide the development of serious games through a systematic process by using an iterative and incremental process applying the phases of context identification, user requirements, planning, design, construction of the interaction devices and video game, and evaluation. ConclusionsThis proposed framework will provide developers of serious games a systematic process with standardized elements for the development of flexible and adaptable software with a high level of patient commitment, which will effectively contribute to their rehabilitation process.